Analytic solution of electromagnetic transient in a polyphase transmission system. - Jingke, Chen
For the first time, this paper gives analytic solutions in the time domain and natural frequencies of nonsymmetrical exciting system after solving the matrix partial differential equations which describe electromagnetic behavior on polyphase lossy-transmission lines, the frequency dependent parameters of which are considered, by using classical method strictly. It is beneficial to the analysis of principle of protections based on travelling wave and to the proposition of new criteria for protection. To verify the result, an example is taken which is offered by G.W. Smith [1] and solved by Bergeron's method [2]. In the paper, several concepts are given. At the appendix, the correctness of solutions are proved mathematically.